PERBANDINGAN NILAI KEKASARAN PERMUKAAN RESIN TERMOPLASTIK POLIAMIDA YANG DIRENDAM LARUTAN SODIUM HIPOKLORIT DAN ALKALIN PEROKSIDA - Andreas Winardhi; Debby Saputra; Dewi Puspitasari (Dentin, 2017)
ABSTRACT  Background: Thermoplastic polyamide resin or nylon is known to be used as a denture base because it has advantages that the color matches the gums, flexible and biocompatibility. Denture materials are related to denture cleanser include sodium hypochlorite and alkaline peroxide. Purpose: To compare the change in  the value of surface roughness of thermoplastic polyamide resin soaked in a solution of sodium hypochlorite and alkaline peroxide. Method: This study was purely experimental research design with post-test only with control group design. The samples used in the study is a thermoplastic polyamide resin square plate 20x20x3 mm based on the specifications of the ADA (American Dental Association) no.12. The samples were divided into three groups: The first treatment group is soaked in sodium hypochlorite, the second treatment group were soaked in alkaline peroxide and a third treatment group were soaked in distilled water. All treatment groups were soaked for 6 days and on sixth day roughness was measured. Result: Roughness measurements obtained the average value of roughness of thermoplastic polyamide resin roughness after immersion sodium hypochlorite (0.550 ± 0.024) was higher than alkaline peroxide (0.346 ± 0.018) and distilled water as a control (0.255 ± 0.013). This is due to changes in the structure and physical properties of the thermoplastic resin, resulting in increased surface roughness. The results of the analysis of all the group treated with post-hoc LSD test obtained P = 0.000 (P <0.005), then there is a significant difference between sodium hypochlorite with distilled water, alkaline peroxide with distilled water and sodium hypochlorite with alkaline peroxide. Conclusion: the value of the surface roughness soaked in sodium hypochlorite higher than alkaline peroxide and distilled water after 6 days.  Keywords: Alkaline Peroxide, Sodium Hypochlorite, Surface Roughness, Thermoplastic Polyamide Resin  ABSTRAK  Latar belakang:Resin termoplastikpoliamida atau dikenal dengan nilon digunakan sebagai bahan basis gigi tiruan, karena memiliki beberapa kelebihan yaitu warnanya sesuai dengan warna gusi, fleksibel dan biokompatibilitas. Bahan gigi tiruan berhubungan dengan bahan pembersih antara lain sodium hipoklorit dan alkalin peroksida. Tujuan:Untuk membandingkan perubahan nilai kekasaran permukaan resin termoplastik poliamida yang direndam dalam larutan sodium hipoklorit dan alkalin peroksida. Metode: yang digunakan dalam penelitian ini adalah penelitian eksperimental murni dengan rancangan post-test only with control group design. Sampel yang digunakan dalam penelitian adalah plat resin termoplastikpoliamida yang berbentuk persegi 20x20x3 mm berdasarkan spesifikasi ADA (American Dental Association) no.12. Sampel dibagi menjadi 3 kelompok yaitu kelompok perlakuan pertama yang direndam sodium hipoklorit,  kelompok perlakuan kedua yang direndam alkalin peroksida dan kelompok perlakuan ketiga yang direndam akuades. Semua kelompok perlakuan direndam selama 6 hari dan pada hari ke 6 dilakukan pengukuran kekasaran permukaan. Hasil: Pengukuran kekasaran didapatkan rerata nilai kekasaran termoplastik poliamida dengan perendaman sodium hipoklorit 6 hari (0,550 ± 0,024) lebih tinggi dibandingkan alkalin peroksida (0,346 ± 0,018) dan akuades sebagai kontrol (0,255 ± 0,013). Hasil analisis semua kelompok perlakuan denga nuji post-Hoc LSD didapatkan P=0,000 (P<0,005) maka terdapat perbedaan bermakna antara sodium hipoklorit dengan akuades, alkalin peroksida dengan akuades dan sodium hipoklorit dengan alkalin peroksida. Kesimpulan: dari penelitian adalah terdapat perbandingan nilai kekasaran permukaan yang direndam dalam sodium hipoklorit alkalin peroksida dan akuades setelah 6 hari.  Kata-kata Kunci: Alkalin Peroksida, Kekasaran Permukaan, Sodium Hipoklorit, Resin Termoplastik Poliamida